2017
DOI: 10.1101/195586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling of autonomic and central events during sleep benefits declarative memory consolidation

Abstract: While anatomical pathways between forebrain cognitive and brainstem autonomic nervous centers are well defined, autonomic-central interactions during sleep and their contribution to waking performance are not understood. Here, we analyzed simultaneous central activity via electroencephalography (EEG) and autonomic heart beat-to-beat intervals (RR intervals) from electrocardiography (ECG) during wake and daytime sleep. We identified bursts of ECG activity that lasted 4-5 seconds and predominated in non-rapid-ey… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Delta wave generation may be a protective mechanism that isolates injured regions from the rest of the brain for neural healing (Naviaux, 2019). Delta wave activity is a normal feature of deep (“slow‐wave”) sleep in which parasympathetic autonomic tone is high and associated with metabolic patterns that underpin healing and repair in both the CNS and periphery (Javaheri & Redline, 2012; Naji, Krishnan, McDevitt, Bazhenov, & Mednick, 2019; Xie et al, 2013; Yüzgeç, Prsa, Zimmermann, & Huber, 2018). In the periphery, slow‐wave sleep is required for normal protective and restorative decreases in blood pressure and the sleep‐associated increase in healthy heart rate variability (Boudreau, Yeh, Dumont, & Boivin, 2013; Javaheri & Redline, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Delta wave generation may be a protective mechanism that isolates injured regions from the rest of the brain for neural healing (Naviaux, 2019). Delta wave activity is a normal feature of deep (“slow‐wave”) sleep in which parasympathetic autonomic tone is high and associated with metabolic patterns that underpin healing and repair in both the CNS and periphery (Javaheri & Redline, 2012; Naji, Krishnan, McDevitt, Bazhenov, & Mednick, 2019; Xie et al, 2013; Yüzgeç, Prsa, Zimmermann, & Huber, 2018). In the periphery, slow‐wave sleep is required for normal protective and restorative decreases in blood pressure and the sleep‐associated increase in healthy heart rate variability (Boudreau, Yeh, Dumont, & Boivin, 2013; Javaheri & Redline, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within each continuative and undisturbed 3-min bin, the mean and standard deviation of RR were calculated, and HR bursts were identified as the RR intervals shorter than 1.25 standard deviations below the mean. We investigated EEG changes during 20-sec windows around the HR bursts because EEG fluctuation typically returned to baseline level within 20 seconds in the previous study from our group (Naji et al, 2019). No other burst occurred in the 20 second windows around the HR bursts.…”
Section: Hr Burst Detectionmentioning
confidence: 99%
“…Additionally, ECG activity has been shown to modulate sleep spindle phase (Brandenberger et al, 2001;Lecci et al, 2017). More recently, our group evaluated changes in EEG and ECG signals that occurred during brief acceleration in heart rate during daytime nap (Naji et al, 2019). Naji et al (2019) identified cardiovascular events during NREM sleep, termed heart rate bursts (HRBs), that last 2-3 seconds and occur mostly in Stage 2 and SWS (Naji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations